2021
DOI: 10.1186/s12875-021-01488-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and comparability of older multimorbid patients with polypharmacy and general practitioners participating in a randomized controlled primary care trial

Abstract: Objectives Recruiting general practitioners (GPs) and their multimorbid older patients for trials is challenging for multiple reasons (e.g., high workload, limited mobility). The comparability of study participants is important for interpreting study findings. This manuscript describes the baseline characteristics of GPs and patients participating in the ‘Optimizing PharmacoTherapy in older multimorbid adults In primary CAre’ (OPTICA) trial, a study of optimization of pharmacotherapy for multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…The FIRE project is mostly limited to the Swiss German speaking part of Switzerland, and it is not a random sample, as GPs self-select into the project by voluntary participation. However, a recent study showed that the GPs participating in the FIRE project are comparable to the entire GP workforce in Switzerland in terms of age, work experience, sex, and work percentage ( Jungo et al, 2021 ). Despite this, since GPs self-select to join the FIRE project, we would like to highlight that there may be several unmeasured differences between the GPs who participate in the FIRE database and those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…The FIRE project is mostly limited to the Swiss German speaking part of Switzerland, and it is not a random sample, as GPs self-select into the project by voluntary participation. However, a recent study showed that the GPs participating in the FIRE project are comparable to the entire GP workforce in Switzerland in terms of age, work experience, sex, and work percentage ( Jungo et al, 2021 ). Despite this, since GPs self-select to join the FIRE project, we would like to highlight that there may be several unmeasured differences between the GPs who participate in the FIRE database and those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, these percentages of being unsure were <10% (10, 14-18). A higher willingness was observed in high-income countries as compared to low-middle-income countries (n = 12, ANOVA, F 15.426, p-value 0.002), with highest percentages in the USA (average 91%) (16,19), followed by Australia (88%) (18), and European countries (average 87%) (8,10,14,15,17,20,21). Intermediate precentages were seen in Singapore (83%) and Ethiopia (82%) (11,22), whereas the lowest percentages were observed in Nepal and Malaysia (57%, 68%) (6,13).…”
Section: Differences In Attitudes At Contextual Levelmentioning
confidence: 93%
“…The response rate was approximately 20%, so the external validity of the study findings may be limited if survey respondents were not representative of the German-speaking Swiss GP population. While GP mean age, work location and setting closely matched the characteristics of the GPs included in the FIRE database and the Swiss GP population, with 44% female GPs were overrepresented in this study (women account for only 35% of the FIRE database and 36% of the Swiss GP workforce) [ 45 ]. Finally, it is also possible that the questionnaire was mostly completed by GPs with a special interest in depression, which may introduce bias.…”
Section: Discussionmentioning
confidence: 92%